Discussion paper on an organizational and management perspective towards business model of traceability and sustainable chemicals in the leather supply chains - Ann-Cathrin Jöst (Hochschule Darmstadt, Fachbereich Wirtschaft, Zentrum für Nachhaltige Wirtschafts- und Unternehmenspolitik ZNWU, 2023)
The production of leather goods requires different chemicals. To align with sustainable consumption and production standards, these chemicals should have no negative effects on the environment and people who are producing and consuming these products. The proliferation of more sustainable chemicals across the leather industry is partially driven by novel mandatory regulations like EU REACH, and partially by the emergence of new voluntary industry standards. At the same time, there are barriers, which can keep companies from becoming more sustainable such as the orientation towards more short-term goals or limitations of the industries' existing infrastructures. Another barrier is a lack of data on current chemical use, which is needed to identify where and how chemicals must be exchanged. While extending efforts to enable traceability can generate this data, a change towards more sustainable chemicals must be supported through a business case to succeed. Without a business case, companies involved will not put in the required additional effort. This paper illustrates that such a business case is difficult to create because of challenges emanating from the complexity of global leather supply chains and its regulatory environment. To understand what bottlenecks exist, this paper made use of a qualitative approach and interviewed 10 different actors in the leather supply chain. Through an interview series, it could be identified that an interest in full chemical traceability and the uptake of more sustainable chemicals exists. However, to realize this uptake there should be harmonized standards and tools on sustainability reporting. In addition, more traceability and changes in chemicals might more likely apply if supply chain partnerships are based on long-term relationships, in which financial support for changes and reporting efforts or the longevity of a business case can sustain. Simultaneously, more discussions and communication should take place between all actors in the supply chain. That is because most changes seem to be demanded by brands, which tend to give little say to other actors and their needs i.e., hide, leather and chemical producers.
Keywords: 330; Leather industry; supply chain; chemicals; sustainability; traceability